KAJIAN LITERATUR PERMODELAN SEDIMENTASI SUNGAI - Usup, Yehezkiel Imanuel; Nomeritae, Nomeritae; Kamiana, I Made (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
Sedimentation in the flow of the river must occur, one of the causes of this sedimentation process is the currents and ebb and flow of water. Tides are fluctuations in sea level due to the attractive force of objects in the sky, especially the sun and moon on the mass of seawater on earth (Triadmodjo, 1999). Air circulation due to tidal currents can carry sediment material contained in these waters so currents and tides in water will affect the distribution of sediment in these waters. The purpose of this research is to examine the literature regarding sedimentation that occurs in river bodies. This research method uses descriptive quantitative research methods with a literature review approach. The stages of the research were carried out starting from article collection, article reduction, discussion, and conclusions. The data sources for this research were in the form of national journal articles in the last 10 years (2013-2022). The results of this literature review show that of the 12 articles reviewed, 8 articles were found that were relevant to the research objectives